Cu-Sn Thin Film as Anode for Thin Film Rechargeable Lithium-Ion Batteries - Polat, B. D.; Sezgin, N.; Keles, O.; Kazmanli, K.; Abouimbrane, A.; Amine, K. (The Electrochemical Society, 2013)
We investigated the anode performance of Cu-Sn flat thin film. The results show that the presence of copper improves the cycleability of the thin film since the mechanical tolerance of the thin film against the stress generated during the high volumetric changes in lithiation/delithiation processes is increased. However, some improvement in the microstructure of the thin film is still required to minimize the quantity or the sizes of Sn particles in thin film and facilitate lithium movements in thin film structure.